LA COMPETITIVIDAD EDUCATIVA (2016)
This essay aims, educational competitiveness, from the ratio of two items of interest: competitiveness and education. Thus, a theoretical proposal that considers analytical approaches, definitions of competitiveness and education set. The competitiveness of a company, a nation or a region is related to the interaction between higher education and the state of technology, so it is necessary to fully exploit the innovation-driven to absorb, adapt, create technology phase, ie an interaction between human capital accumulations, technological change at the university level in companies.